2012
DOI: 10.1016/j.bbcan.2011.10.008
|View full text |Cite|
|
Sign up to set email alerts
|

The role of CXC chemokines in the transition of chronic inflammation to esophageal and gastric cancer

Abstract: Chronic inflammation may increase the risk to develop cancer, for instance esophagitis or gastritis may lead to development of esophageal or gastric cancer, respectively. The key molecules attracting leukocytes to local inflammatory sites are chemokines. We here provide a systematic review on the impact of CXC chemokines (binding the receptors CXCR1, CXCR2, CXCR3 and CXCR4) on the transition of chronic inflammation in the upper gastrointestinal tract to neoplasia. CXCR2 ligands, including GRO-α,β,γ/CXCL1,2,3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 176 publications
(268 reference statements)
0
62
0
Order By: Relevance
“…[110][111][112] Infiltrating neutrophils have also been shown to contribute to the pool of IL8 thereby facilitating the progression of BE and EAC. 113 Nguyen et al in their study demonstrated a relation between increased IL8 expression and poorer prognosis in esophageal cancer confirming the pro-tumoral role of IL8. 114 Thus our previous work and these studies promoted us to further examine the effect of IL8 pathway inhibition in esophageal cancer.…”
Section: Reflux Disease Barrett's Esophagus (Be) and Esophageal Adenmentioning
confidence: 82%
“…[110][111][112] Infiltrating neutrophils have also been shown to contribute to the pool of IL8 thereby facilitating the progression of BE and EAC. 113 Nguyen et al in their study demonstrated a relation between increased IL8 expression and poorer prognosis in esophageal cancer confirming the pro-tumoral role of IL8. 114 Thus our previous work and these studies promoted us to further examine the effect of IL8 pathway inhibition in esophageal cancer.…”
Section: Reflux Disease Barrett's Esophagus (Be) and Esophageal Adenmentioning
confidence: 82%
“…Some chemokines promote conditions favorable for tumor growth and progression, while others have antitumor activity [252]. For example, IL8/CXCL8 induces leukocyte cell migration during inflammation, and this response can promote tumor growth and development by generating a favorable microenvironment [252, 253]. …”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…Previous studies, utilizing the zebrafish model system, have shown that Cxcr2 receptor signaling axis is involved in both long-range systemic neutrophil mobilization from hematopoietic tissue as well as local recruitment to infection or purified Cxcl8 (IL-8, a potent Cxcr2 ligand) [17], [18]. Previous studies have also implicated CXCR2 signaling in tumor progression [21], [22], [24][29]. CXCR2 expression is increased in some tumor types [26], [30][32] and pharmacological inhibition of CXCR1 and CXCR2 inhibits neutrophil recruitment into A547 lung tumor spheroids resulting in slower tumor growth [33].…”
Section: Introductionmentioning
confidence: 99%